Biorational Management of Root-knot Nematode (Meloidogyne incognita) in Ginger (Zingiber officinale Rosc.) (Indian Journal of Nematology, 2025)
The current investigation was conducted to document the nematode species associated with Zingiber officinale and to formulate a biorational management approach against the predominant nematode through the application of biocontrol agents and green plant materials. A survey revealed that Meloidogyne incognita (Prominence value 13.98) was the most prevalent nematode in ginger-growing areas of Thiruvananthapuram, Kollam, and Idukki districts of Kerala, followed by Rotylenchulus reniformis (Prominence value 9.60). Microplot studies were conducted to investigate the effect of biocontrol agents (Pseudomonas fluorescens, Trichoderma asperellum, Bacillus macerans, and Purpureocillium lilacinum) as rhizome treatment, applied either alone or in combination with gliricidia as green leaf mulch, in three consecutive years (2018–2020) at Instructional Farm, Vellayani. Among the treatments, the application of a talc-based formulation of P. lilacinum (cfu 2×108) @ 3%w/w along with gliricidia leaf mulching @ 1 kg/m2, exhibited significant superiority in lowering the nematode population in the soil (83.89% reduction over untreated). Furthermore, the rhizome treatment using T. asperellum in combination with mulching of gliricidia green leaves, proved to be equally effective to the combined application of P. lilacinum rhizome treatment and green leaf mulching with gliricidia in decreasing the nematode population in the root (80.43 to 86.96% reduction over untreated) and enhancing the yield (49.43 to 66.45% increase over untreated). A similar trend was observed in root-knot index as well. The results of the study clearly indicate the effectiveness of biocontrol agents as rhizome treatment and the adoption of locally sourced green foliage as a mulching strategy in managing M. incognita in ginger, thereby encouraging natural resource conservation through low-cost technologies. Further, the risks associated with environmental repercussions resulting from synthetic chemicals can be eliminated and thus more sustainable alternatives for the management of plant parasitic nematodes can be achieved.